PENGARUH PROFESIONALISME GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMA NEGERI 1 PARIANGAN KABUPATEN TANAH DATAR - Alwi Alwi (IAIN Batusangkar, 2018)
This study was conducted to determine the effect of professionalism and teacher motivation on teacher performance at SMAN 1 Pariangan, Tanah Datar. The research question is” is there any effect of professionalism and teacher motivation on teacher performance. There are 3 measuring tools in this research that is teacher professionalism, motivation, and teacher performance”. Data obtained from 35 responden who teach in SMAN 1 Pariangan. Researcher used questionnaire to gather the data for this research. For data analysis, researcher used descriptive and multiple regression technique. Through multiple regression techniques that used for hypothesis testing, the results showed that professionalism seignificantly improved teacher performance, while motivation did not significantly influence teacher performance. In addition, if the two variables are processed simultaneously, it is found that professionalism along with motivation can improve teacher performance with value R2 equal to 55,8%. The value of β for professional variables on means performance is 0.479 which means that each increase in professionalism value by one point increases the teacher’s performance value by 0.479.